Effectiveness of a New Device for Hand, Wrist, and Forearm Rehabilitation: Feasibility Randomized Controlled Trial - Adriana M Ríos Rincón; Christine Guptill; Yilina Liubaoerjijin; Mathieu Figeys; Farnaz Koubasi; Geoffrey Gregson; Antonio Miguel Cruz (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundForearm, wrist, and hand impairments affect many individuals and impose a significant economic burden on health care systems. The FEPSim (flexion, extension, pronation, and supination) is designed for hand and wrist rehabilitation. It could become part of the standard care for upper extremity rehabilitation, aiming to improve range of motion, dexterity, and strength during therapeutic activities. However, the FEPSim has not yet been tested in a health care setting, highlighting the need for a trial to assess its effectiveness in upper extremity rehabilitation. ObjectiveWe aim to assess the feasibility of conducting a definitive trial investigating the effectiveness of adding a new device for hand therapy exercises, the FEPSim, to standard care for patients with impairments of the hand, wrist, and forearm. MethodsThirty-eight patients with impairments of distal upper extremities were randomly assigned either to the intervention group (FEPSim and standard care, n=19) or to the control group (standard care, n=19). Therapeutic activities to increase strength, range of motion, resistance, and dexterity were delivered by treating hand therapists using the FEPSim device for the intervention group. Outcome measures included wrist passive and active range of motion, grip strength, pinch grip force, and the Patient-Rated Wrist Evaluation. ResultsThe trial retention rate (36/38, 95%) and compliance (control group: 100%; intervention group: 89%) were high. The comparisons of the change-from-baseline between groups revealed that in 63.2% (12/19) of the outcome variables, the change was in favor of the FEPSim, with statistically significant improvements in passive wrist flexion (t34Pt34P ConclusionsThe FEPSim was accepted as part of standard care by therapists and patients at 2 hospitals. The trial design was feasible for hand intervention using the FEPSim device. The FEPSim positively affected grip strength, an objective measure of hand functioning.